A study on severely cold-rolled and intermediate temperature aged HfNbTiZr refractory high-entropy alloy. (November 2020) - Tu, Chun-Hsiang; Wu, Shyi-Kaan; Lin, Chieh
Abstract: A single-phase body-centered cubic (BCC) HfNbTiZr refractory high-entropy alloy (RHEA) was fabricated by vacuum arc melting. The effect of aging at 450 °C on 80% cold-rolled HfNbTiZr specimens (abbr. as CRA) as well as that on 80% cold-rolled and then recrystallized at 1000 °C for 1 h (abbr. as CRRA) have been investigated. A significant increase of hardness after aging at 450 °C was presented in both CRA and CRRA specimens. The hardness of CRA specimens increased dramatically within a shorter time than that of CRRA specimens, indicating that the cold-rolled process can significantly enhance the age hardening effect. During aging at 450 °C, BCC and hexagonal closed-packed (HCP) precipitates formed in the BCC matrix. The particle-like Nb-rich BCC precipitates were mainly within the grains and needle-like HfTiZr HCP precipitates mostly located near the grain boundaries. In CRA specimens aged for 500 h, BCC precipitates could grow up to 30–90 nm in radius and HCP precipitates to 300–1600 nm in length and 40–140 nm in width. The results of tensile test revealed that the presence of the precipitates can induce brittleness in HfNbTiZr alloy. Highlights: The hardness of HfNbTiZr increases significantly after aging at 450 °C. BCC and HCP precipitates can form in the BCC matrix during aging. The cold rolling process can significantly enhance the age hardening effect. HCP precipitates are mostly observed near the GBs and BCC precipitates are mainly within the grains.